Doing business 2013 smarter regulations for small and medium-size enterprises. (Doing business, 2013)
Tenth in a series of annual reports comparing business regulation in 185 economies, Doing Business 2013 measures regulations affecting 11 areas of everyday business activity: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, closing a business, and employing workers. The report updates all indicators as of June 1, 2012, ranks economies on their overall "ease of doing business", and analyzes reforms to business regulation -- identifying which economies are strengthening their business environment the most. The Doing Business reports illustrate how reforms in business regulations are being used to analyze economic outcomes for domestic entrepreneurs and for the wider economy. This year marks the tenth anniversary of the global Doing Business report. Doing Business is a flagship product by the World Bank and IFC that garners worldwide attention on regulatory barriers to entrepreneurship. More than 60 economies use the Doing Business indicators to shape reform agendas and monitor improvements on the ground. In addition, the Doing Business data has generated over 870 articles in peer-reviewed academic journals since its inception. This year's report includes two new economies: Barbados and Malta